Rice market monitoring and policy options study - Goletti, Francesco; Ahmed, Raisuddin; Minot, Nicholas; Berry, Philippe; Bautista, Romeo M.; Nguyen, Viet Hai; Nguyen, The Binh (International Food Policy Research Institute, 1996)
Through a survey of approximately 1300 farmers, millers and traders, this study undertook an in-depth investigation of the rice marketing system in the midst of its transition from a centrally planned to a market-based economy. Its findings suggest strong private sector response to the reforms yet a number of remaining constraints to its further expansion. Its main policy implication is that liberalization of external trade (quota removal) and internal trade would lead to considerable income gain for the country, while benefitting farmers and the rural poor. Over the course of the project, several outreach activities were conducted, including several training modules in food policy analysis with participants from MARD and other government agencies, numerous workshops and seminars in Hanoi and other provinces, dissemination with international media, and publications.